Case Report: Cardiac transplantation in a 76-year-old recipient: moving from anagraphic to biological age under a geriatric perspective - Giovannico, Lorenzo; Mazzone, Federica; Fischetti, Giuseppe; Parigino, Domenico; Savino, Luca; Leo, Claudia; Cristiano, Giuseppe; Acquaviva, Tommaso; Di Bari, Nicola; Padalino, Massimo; Bottio, Tomaso (Frontiers in Transplantation, 2025)
Background/objectivesHeart transplantation remains the definitive treatment for end-stage heart failure. However, donor shortages and the increasing age of candidates present significant challenges. This report aims to highlight the feasibility and successful outcome of heart transplantation in an elderly patient, questioning traditional age-based eligibility criteria.MethodsA 76-year-old male with idiopathic dilated cardiomyopathy and severe heart failure underwent orthotopic heart transplantation. Preoperative assessments included right heart catheterization, echocardiography, and cardiac index evaluation. A suitable 66-year-old female donor was identified, and transplantation was performed using the bicaval technique. Postoperative outcomes were monitored through echocardiography and biopsy analysis.ResultsThe patient had an uneventful postoperative course, with extubation on day 1 and discharge on postoperative day 30. Follow-up at 14 months showed excellent clinical recovery, with an improved left ventricular ejection fraction (LVEF) of 58% and global longitudinal strain (GLS) of −20.8%. No signs of rejection were observed on biopsy.ConclusionsThis case represents the oldest documented successful heart transplant recipient discharged home. The findings suggest that age alone should not be a limiting factor in transplantation eligibility. Expanding criteria to include well-selected elderly patients could help address the growing demand for donor hearts.